2002
DOI: 10.1046/j.1365-2036.2002.01348.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of rabeprazole, lansoprazole and omeprazole on intragastric pH in CYP2C19 extensive metabolizers

Abstract: SUMMARYAim: To investigate the inhibitory effects on gastric acid secretion of three proton pump inhibitors, omeprazole, lansoprazole and rabeprazole, using a three-way crossover design in healthy Helicobacter pylori-negative, S-mephenytoin 4¢-hydroxylase (CYP2C19) 1 homo-and hetero-extensive metabolizers. Methods: Eight healthy Japanese male volunteers were enrolled. After the administration of rabeprazole (10 mg ⁄ day), lansoprazole (30 mg ⁄ day) or omeprazole (20 mg ⁄ day), intragastric pH monitoring was co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
77
2
7

Year Published

2004
2004
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(90 citation statements)
references
References 22 publications
4
77
2
7
Order By: Relevance
“…A number of investigators have reported that earlier symptom relief and higher endoscopic healing rates have been obtained with PPI in comparison with H2-receptor antagonists (H2-RAs) [11,12] . The time period required to obtain maximal inhibition of gastric acid secretion is, however, reported to differ between PPI [13][14][15][16][17] . The time taken for the resolution of symptoms in patients with reflux esophagitis is, therefore, unlikely to be uniform in all PPI.…”
Section: Introductionmentioning
confidence: 99%
“…A number of investigators have reported that earlier symptom relief and higher endoscopic healing rates have been obtained with PPI in comparison with H2-receptor antagonists (H2-RAs) [11,12] . The time period required to obtain maximal inhibition of gastric acid secretion is, however, reported to differ between PPI [13][14][15][16][17] . The time taken for the resolution of symptoms in patients with reflux esophagitis is, therefore, unlikely to be uniform in all PPI.…”
Section: Introductionmentioning
confidence: 99%
“…Rabeprazole is the drug least metabolized via this enzyme route (10). Studies analyzing the capacity of the different PPIs to suppress gastric acid have shown that the mean pH value with the administration of rabeprazole is not influenced by the CYP2C19 genotypes (10)(11)(12).…”
Section: Discussionmentioning
confidence: 99%
“…The outcome of these rather rigorous inclusion criteria and design was a difficulty in fulfilling our initial goal of recruiting a large cohort of patients. Finally, from a number of candidate PPIs, we chose rabeprazole, since this drug has a number of potential advantages: (a) a rapid onset of action as shown by gastric pH monitoring studies [3,12,13] ; (b) a good safety profile; (c) a lack of drug interactions due to its specificity in terms of hepatic and non-hepatic metabolic pathways [4,5] ; and (d) its effectiveness in the treatment of some symptoms associated with GERD [14] . The results of our study are consistent with other studies of PPI tests which have without exception demonstrated the high sensitivity and poor specificity of this diagnostic approach [1] .…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, when the target population for such PPI tests is considered, the lack of drug interference and the safety profile are both of most importance. In these respects, rabeprazole also displays some pharmacological advantages due to a partly non-hepatic metabolism and a linear response, which result in more predictable effects in terms of acid suppression [4,5] . We therefore aimed to deter mine the diagnostic value of the rabeprazole test in a population of patients followed up by general practitioners (GPs) for symptoms suspected to be reflux-related.…”
Section: Introductionmentioning
confidence: 99%